Characterization of Lactococcus strains isolated from artisanal Oaxaca cheese. (March 2020) - Caro, I.; Quinto, E.J.; Fuentes, L.; Alessandria, V.; Cocolin, L.S.; Redondo-del-Río, M.P.; Mayo, B.; Flórez, A.B.; Mateo, J.
Abstract: Lactococci strains obtained from raw-milk Oaxaca cheese through its production process in two factories from the Tulancingo Valley, Mexico, were isolated and characterized. A total of 120 colonies were selected from the growth in M17 and MRS agars. Twenty were identified as lactococci strains, all Lactococcus lactis, and were characterized by molecular and phenotypic methods including carbohydrate use, enzymatic profile, acidifying capacity, and antibiotic and phage resistance. High phenotypic diversity was observed and confirmed among the Lactococcus lactis strains by rep-PCR fingerprints. Fifty percent of the strains were resistant to streptomycin and 35% to erythromycin. Nine isolates were considered as fast acidifying strains. The predominant volatile compounds produced were 3-methylbutanol, 3-methylbutanal and butane-2, 3-dione. A selection of strains isolated in this study has shown satisfactory characteristics to be used as potential starters for the industrial production of Oaxaca cheese. Highlights: Lactococci strains from Mexican Oaxaca cheese were identified and characterized. Lactococcus lactis spp. isolates showed high phenotypic and molecular diversity. Nine fast-fermenting strains (pH < 5.0 in milk) were found. Strains have technological properties as starters for industrial cheese production.